Statin effects on post-stroke epilepsy and mortality – Taiwan population-based study. (3rd May 2020) - Hsieh, Peiyuan F.; Tung, Hsin; Lin, Ching-Heng
ABSTRACT: Objectives : Statins have anti–inflammatory effects on several neurological diseases. However, their effects on post-stroke epilepsy and mortality have not been well studied. Method : This is a retrospective cohort study, based on the one-million random data from National Health Insurance Research Database (NHIRD) of Taiwan. We identified stroke inpatients during 2000–2009. They were grouped into statin users and non-users, and followed up to 2010. Excluded were those with in-hospital mortality, in-hospital seizure(s), epileptic history, antiepileptic drug use before admission, or age under 45. The hazard ratios of statin-associated epilepsy and mortality were analyzed separately. Results : There were 16, 711 statin non-users and 2246 users. There was no significant differences between the two groups in terms of epilepsy (13.3 vs. 15.7 per 1000 person-years, p = 0.728) and overall mortality (66.3 vs. 104.6 per 1000 person-years, p = 0.351). Subgroup analysis of male patients showed that statin-users had lower mortality risk compared with non-users (60.2 vs. 113.0 per 1000 person-years, p = 0.032). Conclusion : Statins have a modest but non-significant effect in preventing post-apoplectic epilepsy in Taiwan. Statins decrease post-stroke mortality only in men. Further studies are needed to depict their exact roles in these issues.